The malalignment syndrome : diagnosing and treating a common cause of acute and chronic pelvic, limb and back pain /: diagnosing and treating a common cause of acute and chronic pelvic, limb and back pain. (2013) - Schamberger, Wolf; Lane, David; Fraser, Lauren; Stevens, Sarah; Steinberg, Karina
No abstract available